(المناهج المعاصرة للتعليم القرآني في ماليزيا (دراسة تأصيلية تطبيقية = Contemporary curricula for Quranic education in Malaysia (An applied originals study) - Elatrash, Radwan Jamal Yousef; Hasan Ahmed, Mahmood Ahmed; Shukri, Ahmad Khalid; Al-Hamwi Al-Olabi, adnan (IIUM Press, International Islamic University Malaysia, 2020)
تروم هذه الدراسة إلى استكشاف مناهج التدريس القرآني في دولة ماليزيا، وما لها من أدوار حضارية في الحفاظ على الهوية الإسلامية الملايوية، وغرس المفاهيم والقيم الإسلامية في نفوس النشء، وتمكين الهواة منهم من اكتساب مهارات متميزة على المستوى اللغوي، والديني، والخلقي. وذلك من خلال استقراء شبه كامل لما تقوم به مؤسسات تحفيظ وتعليم القرآن الكريم في مختلف المراحل الابتدائية وحتى الدراسات العليا، حيث أكدت الدراسة على أهمية الدرس القرآني في زمن هيمنت عليه قوى الفنون وعلوم التكنولوجيا. كما تسعى هذه الدراسة الجامعة بين النظرية والتطبيق إلى اكتشاف الهدف التعليمي القرآني وما له من دور في صناعة الشخصية الدينية المتألقة والمتفاعلة في المجتمع الماليزي، وبيان دورها التاريخي في تقديم الحلول الاجتماعية المتراكمة. وكان المنهج الملائم لطبيعة هذا البحث هو المنهج الاستقرائي لجمع الأفكار المبثوثة في ثنايا مناهج التحفيظ، ثم المنهج الوصفي، والمنهج التحليلي الإحصائي الذي يحتاج إلى مكابدة عقلية شاملة لدراسة مناهج قرآنية غير عربية وفهمها، ثم القيام بترتيبها وتصنيفها ومقارنتها بغيرها من أجل استنباط معالم ثابتة لتقويمها، وتصحيح مسارها التربوي. ومن نتائج البحث: مراعاة البرامج التعليمية _ في هذه المؤسسات _ للطالب الماليزي علميًّا وسلوكيًّا، ومنها: مراعاة القائم على عملية التَّعَلّمِ _ الأستاذ _ وذلك بتأهيله علميًّا ومهاريًّا وتربويًّا، من خلال برامج مُعَدَّة لهذا الغرض. كما توجد جملة أهداف أخرى ترعى الوسائل التعليمية المتنوعة، والمناهج المتبعة في العملية التعليمية. ******************************************************************************************* This study aims to explore the world of memorization and the curricula of Quranic teaching in the state of Malaysia, and what the civilized roles it plays in preserving the Malay Islamic identity, instilling Islamic concepts in the hearts of young people, and enabling amateurs to acquire distinguished skills at the linguistic, religious, and moral level. This happens through a study of what the departments of Quranic education are doing in the various primary and even graduate levels, where the study emphasized the importance of the Quranic lesson in a time dominated by the forces of arts and technology sciences. This study, which combines theory and practice, also seeks to discover the Quranic educational goal and its role in making the splendid and interacting religious personality in Malaysian society and clarify its historical role in providing a solution to accumulated social problems. The appropriate approach to the nature of this research is the inductive approach to gather the ideas expressed in the folds of memorization approaches, then use the descriptive and analytical method, which requires a comprehensive mental endeavor to study and understand non-Arab Qur'anic curricula, then arrange, classify and compare them with others in order to derive consistent features for their evaluation and correct their educational path.